In vitro antidermatophytic activity of bioactive compounds from selected medicinal plants - Daisy Savarirajan (SpringerOpen, 2021)
Abstract Fungal infections are among the most difficult diseases to manage in humans. Eukaryotic fungal pathogens share many similarities with their host cells, which impairs the development of antifungal compounds. Therefore, it is desirable to harness the pharmaceutical potential of medicinal plants for antifungal drug discovery. In this study, the antifungal activity of sixteen plant extracts was investigated against selected dermatophytic fungi. Of the sixteen plants, the cladode (leaf) of Asparagus racemosus, and seed extract of Cassia occidentalis showed antifungal activity against Microsporum gypseum, Microsporum nanum, Trichophyton mentagrophytes and Trichophyton terrestre. The plant antifungal compounds were located by direct bioassay against Cladosporium herbarum. IR and NMR spectrometry analyses of these compounds identified the presence of saponin (in A. racemosus) and hydroxy anthraquinone (in C. occidentalis) in these antifungal compounds. The antidermatophytic activity of plant anthraquinone and saponins with reports of little or no hemolytic activity, makes these compounds ideal for alternative antifungal therapy and warrants further in-depth investigation in vivo.